2008
DOI: 10.1111/j.1570-7458.2008.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Starvation tolerance of macropter brown planthopper, Nilaparvata lugens, from temperate, subtropical, and tropical populations in East and South‐East Asia

Abstract: We compared the starvation tolerance of macropter brown planthopper, Nilaparvata lugens Stål (Homoptera: Delphacidae), a characteristic favoring long-distance migration, among populations collected from subtropical and temperate East Asia, tropical Indochina, and the Malay Peninsula. Starvation tolerance of planthoppers was significantly affected by climatic zone in which the planthoppers had been collected and by feeding duration after adult eclosion. After 24 h feeding on rice, newly emerged macropters origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…BPH strains in different regions show phenotypic variation. Subtropical and temperate East Asian macropters were more adapted to migration with longer pre-oviposition periods and stronger starvation tolerance 14 , while tropical Asian strains (Southern Vietnam, Thailand, Malaysia, Philippines) were more adapted to reproduction 15 . BPH strains in South Asia, Southeast Asia and Oceania showed distinct virulence reactions to some rice varieties 16,17 , which suggests the exists of genetic difference among regional populations.…”
Section: Introductionmentioning
confidence: 99%
“…BPH strains in different regions show phenotypic variation. Subtropical and temperate East Asian macropters were more adapted to migration with longer pre-oviposition periods and stronger starvation tolerance 14 , while tropical Asian strains (Southern Vietnam, Thailand, Malaysia, Philippines) were more adapted to reproduction 15 . BPH strains in South Asia, Southeast Asia and Oceania showed distinct virulence reactions to some rice varieties 16,17 , which suggests the exists of genetic difference among regional populations.…”
Section: Introductionmentioning
confidence: 99%
“…4.2). Further, Wada et al (2009) reported that macropters originated from East Asia were more tolerant to starvation than those from tropical countries. Macropters feed actively on rice for the first 2 or 3 days after eclosion (Tanaka 1999).…”
Section: Natural Enemy Abundancementioning
confidence: 99%
“…Figure 4.3 illustrates a typical example showing the difference in longevity of macropters between temperate and tropical populations, in relation to posteclosion feeding. Taken pre-ovipositional periods into consideration, Wada et al (2009) suggested the difference in resource allocation (vitellogenesis or stored resources) between East Asia and tropical populations: Macropters of East Asia populations invest energy intake from feeding mainly on reserves, which enhance starvation tolerance, while those of tropical populations invest on ovary development as well as stored reserves.…”
Section: Natural Enemy Abundancementioning
confidence: 99%
“…The reproductive status of BPH females has been the main factor used to determine natural population dynamics and ecological infrastructure of BPH females in rice fields (Chelliah et al, 1980), and reproductive status was also related to migration of BPH (Wada et al, 2009). Several indicators and methods have been adopted to evaluate the reproductive status of BPH females, such as ovary dissection and classification, and their pre-oviposition period (Chen et al, 1979;Wada et al, 2007).…”
Section: Discussionmentioning
confidence: 99%